Flt3 Ligand Treatment Attenuates T Cell Dysfunction and Improves Survival in a Murine Model of Burn Wound Sepsis. Issue 1 (January 2017) - Patil, Naeem K.; Bohannon, Julia K.; Luan, Liming; Guo, Yin; Fensterheim, Benjamin; Hernandez, Antonio; Wang, Jingbin; Sherwood, Edward R.
ABSTRACT: Introduction: Sepsis is a leading cause of death among severely burned patients. Burn injury disrupts the protective skin barrier and causes immunological dysfunction. In our previous studies, we found that burn injury and wound infection causes a significant decline in lymphocyte populations, implying adaptive immune system dysfunction. In the present study, we examined the effect of treatment with Fms-like tyrosine kinase-3 Ligand (Flt3L) on T cell phenotype and function in a model of burn wound sepsis. FLt3L is an essential cytokine required for hematopoietic progenitor cell development and expansion of both myeloid and lymphoid lineages. Flt3L has been shown to potentiate innate immune functions of dendritic cells and neutrophils during burn wound sepsis. However, the ability of Flt3L to improve T cell function during burn wound sepsis has not been previously evaluated. Methods: Mice underwent 35% total body surface area scald burn and were treated with Flt3L (10 μg) or vehicle daily via the intraperitoneal route starting 1 day after burn injury. On day 4 after burn injury, Pseudomonas aeruginosa was used to induce wound infection. Leukocytes in spleen and wound draining lymph nodes were characterized using flow cytometry. Bacterial clearance, organ injury, and survival were also assessed. Results: Flt3L treatment prevented the decline in splenic CD4 + and CD8 + T cells caused by burn injury and infection. Flt3L treatment also attenuated the decline in CD28 expression on CD4 + and CD8 + T cells and IFNγ production by CD8 + T cells in the spleen and wound draining lymph nodes. Furthermore, Flt3L decreased the levels of programmed death ligand 1 expression on splenic dendritic cells and macrophages. Flt3 treatment improved systemic bacterial clearance, decreased liver and kidney injury, and significantly improved survival in mice with burn wound sepsis. Conclusion: Burn injury and associated sepsis causes significant loss of T cells and evidence of T cell dysfunction. Flt3L attenuates T cell dysfunction and improves host resistance to burn wound sepsis in mice.